2022
DOI: 10.5005/jp-journals-10006-2084
|View full text |Cite
|
Sign up to set email alerts
|

A Study and Analysis of Cesarean Sections by Robson\'s Ten Group Classification System

Abstract: Background:The hitherto rising rate of cesarean sections is affecting women's obstetric careers by its inherent operative complications and on the other hand, the fetal complications arising from morbid trials of labor has its own medicolegal repercussions. In this scenario, Robson's Ten Group Classification System (TGCS) provides a comprehensive and conclusive system for classifying indications of cesarean sections and helps to curb down rates of cesarean sections. Methodology: The present study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…[9][10][11] [12][13][14][15][16] The major contributors to CS were similar to study by Deshmukh et al at Maharashtra and at Bellary where groups 5, 1 and 2 were the highest. 17,10 Analysis of indications revealed that foetal distress was the commonest in groups 1 to 4 which was similar to study at Belgavi while the study by Murugesan et al past dates and oligohydramnios were the commonest. 11,18 In group 5 the commonest indication was previous CS and in group 10 amniotic fluid disorders was commonest which was in line with several studies.…”
Section: Discussionsupporting
confidence: 71%
“…[9][10][11] [12][13][14][15][16] The major contributors to CS were similar to study by Deshmukh et al at Maharashtra and at Bellary where groups 5, 1 and 2 were the highest. 17,10 Analysis of indications revealed that foetal distress was the commonest in groups 1 to 4 which was similar to study at Belgavi while the study by Murugesan et al past dates and oligohydramnios were the commonest. 11,18 In group 5 the commonest indication was previous CS and in group 10 amniotic fluid disorders was commonest which was in line with several studies.…”
Section: Discussionsupporting
confidence: 71%